USE OF ENGINEERING PROGRAMS IN THE PROCESS OF TEACHING PHYSICS (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
This article analyzes the problems that arise in the process of research, practical and laboratory work of students in physics, as well as the advantages and solutions of these problems using virtual software, and the possibility of performing practical and laboratory work using Multisim. and information on methods.